The Implementation of Genetic Algorithm in The Vehicle KIR Test Scheduling System - Suprihadi Suprihadi; Rama Aufadha Risqullah (Universitas Raharja, 2021)
Based on the results of observations and data collection, the vehicle parking test services at the Salatiga City Transportation Agency have not implemented a structured scheduling system in managing their service schedules. This has resulted in an accumulation of the number of vehicles that exceed the service capacity on a working day. Therefore, a scheduling system is needed to assist the agency in arranging the due time schedule for the KIR test of a vehicle, and helping the vehicle owner community to find out the due time for the next KIR test. The scheduling method used is a genetic algorithm that is applied to a web-based application. The application is built using the PHP language and MySql database. With this website-based scheduling system application, it has made it easier for service officers to manage the KIR test service schedule, especially if there is a change in the number of vehicles.